2015
DOI: 10.1016/j.ijsu.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Advanced laparoscopic fellowship training decreases conversion rates during laparoscopic cholecystectomy for acute biliary diseases: A retrospective cohort study

Abstract: Formal advanced laparoscopic fellowship training may decrease length of stay among patients presenting with acute biliary pathology who undergo laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
3
23
0
1
Order By: Relevance
“…In human medicine, MIS experience and level of training influences complications and conversion to open laparotomy. 22,23 While cases included in this study may have been part of the learning curve for multiport laparoscopy (and LAG) for some surgeons and/or residents, as evidenced by a high abdominal access complication rate, we believe our procedural complication and conversion rate is low, consistent with previous reports of LAG. 10,16 We had an overall postoperative complication rate of 34% (15/44).…”
Section: Discussionsupporting
confidence: 86%
“…In human medicine, MIS experience and level of training influences complications and conversion to open laparotomy. 22,23 While cases included in this study may have been part of the learning curve for multiport laparoscopy (and LAG) for some surgeons and/or residents, as evidenced by a high abdominal access complication rate, we believe our procedural complication and conversion rate is low, consistent with previous reports of LAG. 10,16 We had an overall postoperative complication rate of 34% (15/44).…”
Section: Discussionsupporting
confidence: 86%
“…In a similar study comparing consultant surgeons, trainee surgeons, and trained surgeons, the authors found that there were no differences among the three groups in conversion rates, bile duct injury rates, general complication rates, or length of stay; however, the duration of operation in the trainee surgeons was significantly longer compared to the other two groups [21]. In the setting of LC for acute cholecystitis, Abelson et al reported that advanced laparoscopic fellowship-trained surgeons had significantly lower conversion rate and shorter operative time than the nonfellowship-trained surgeons; however, the complication rates were not significantly different [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Failure of the contrast to opacify the common hepatic duct and the right and left hepatic ducts would signal the surgeon that the CBD, not the cystic duct, has been cannulated [74]. The use of IOC is associated with a 62% reduction in CTO rate (OR = 0.38, 95% CI: 0.17-0.94; P = 0.04) [75]. If IOC does not facilitate unmistakeable biliary ducts recognition, then CTO is indicated [74].…”
Section: Intraoperative Patient-related Risk Factorsmentioning
confidence: 99%
“…Surgeon's knowledge, laparoscopic fellowship training, operative experience and skills in laparoscopic surgery play an important role in timely recognition of the need for CTO and are important predictors for CTO [49,74,75,78]. Surgical registrars (postgraduate year 4-5) have a twofold higher rate of CTO (OR = 1.7; 95% CI: 1.1-2.5; P = 0.0067) than surgical consultants [25].…”
Section: Surgeon-related Risk Factorsmentioning
confidence: 99%